FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN PERUSAHAAN MANUFAKTUR BURSA EFEK INDONESIA - Anggelina Margareta Riamelia Montolalu; Ventje Ilat; Novi Swandari Budiarso (Universitas Sam Ratulangi, 2022)
This study aims to determine the effect of Financial Distress, Debt Default, and Profitability on Going Concern Audit Opinion of Manufacturing Company on Bursa Efek Indonesia (2016-2019). The data sample in this study were obtained using purposive sampling techniques and generated 35 data, namely 5 years of timeseries data and 7 companies. This study was analyzed using Non Parametric Chi Square. The result showed that: (1) Financial Distress have a positive effect on the Going Concern Audit Opinion of Manufacturing Company on Bursa Efek Indonesia during 2016-2019 with percentage value of 40.50%. (2) Debt Default have a positive effect on the Going Concern Audit Opinion of Manufacturing Company on Bursa Efek Indonesia during 2016-2019 with percentage value of 57.70%. (3) Profitability (Return On Asset) have a negative effect on the Going Concern Audit Opinion of Manufacturing Company on Bursa Efek Indonesia during 2016-2019 with percentage value of 29.60%.